CHRONIC RENAL FAILURE WITH GASTROPATHY UREMICUM AND HYPERTENSIVE RENAL DISEASE ON 34 YEARS OLD WOMAN - Chenso Sulijaya (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Chronic renal failure (CRF), also known as chronic kidney disease (CKD), defined as abnormalities of renal pathology, such as hematuria and/-or proteinuria, or decreased GFR <60 mL/mi/1.73 m2 for more than 3 months. 34 years old woman, comes with hematemesis 1 week before hospital admission. The patient felt weak, headache, and dizzy, this complaint has been felt since 4 months and felt diminished urination, a month before admission there are ascites and leg edema with 160/100 mmHg of bloodpressure. Patients diagnosed with CRF ec primary glomerulopati, gastropathy uremicum, anemia ec CRF compounded with upper gastrointestinal bleeding. The management was based on stage the decrease of glomerular filtration rate, which is in principle divided into conservative therapy and renal replacement therapy (RRT). It also takes a multidisciplinary therapeutic areas that include medical, social, psychological, nutritional, and other coverage. The mortality rate in patients with CKD depends on the underlying cause and also the management. [J Agromed Unila 2014; 1(2):145-150]Keywords: ascites, chronic renal failure, glomerular filtration rate, hematemesis, leg edema